1996
DOI: 10.1128/jcm.34.2.398-403.1996
|View full text |Cite
|
Sign up to set email alerts
|

Typing multidrug-resistant Staphylococcus aureus: conflicting epidemiological data produced by genotypic and phenotypic methods clarified by phylogenetic analysis

Abstract: An outbreak of an unusual tetracycline-sensitive, rifampicin-and ciprofloxacin-resistant, methicillin-resistant Staphylococcus aureus (MRSA) strain at a large teaching hospital was investigated. Two typing methods, phage typing and restriction fragment length polymorphism (RFLP) by pulsed-field gel electrophoresis (RFLP-PFGE), gave conflicting results which were clarified by phylogenetic analysis. Phage typing identified all the ''epidemic-associated'' strains as identical, while RFLP-PFGE further divided thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 14 publications
1
12
0
2
Order By: Relevance
“…Results of a PFGE typing study of Staphylococcus aureus [55] showed that the resolution of this method exceeded that of restriction fragment length polymorphism analysis with ribosomal or toxin A DNA probes and that it did not correlated with epidemiological data.…”
Section: Discriminatory Power Of Pfgementioning
confidence: 96%
“…Results of a PFGE typing study of Staphylococcus aureus [55] showed that the resolution of this method exceeded that of restriction fragment length polymorphism analysis with ribosomal or toxin A DNA probes and that it did not correlated with epidemiological data.…”
Section: Discriminatory Power Of Pfgementioning
confidence: 96%
“…The PFGE was performed as previously described (Jorgensen et al 1996). Briefly, bacterial colonies were inoculated in Brain Heart Infusion and then centrifuged.…”
Section: Pulsed-field Gel Electrophoresismentioning
confidence: 99%
“…PFGE. The PFGE profiles were obtained by the method introduced by Jorgensen et al (1996). Electrophoresis was performed using the CHEF Mapper system (Bio-Rad Laboratories, Hercules, CA) with a switch time increased from 2 s to 35 s over 21 h at 13°C at a constant voltage of 6 V/cm (Santos et al, 1999;de Souza Duarte et al, 2013).…”
Section: Molecular Identification and Fingerprintingmentioning
confidence: 99%